POSITIVE POLITENESS STRATEGIES USED BY THE GUEST IN TRIPADVISOR REVIEW OF PRIME PLAZA SUITES SANUR BALI - Laksmiati, Ni Made Putri; Maharani, Putu Devi; Candra, Komang Dian Puspita (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTThis study entitled Positive Politeness Strategies Used by the Guest in TripAdvisor Review ofPrime Plaza Suites Sanur Bali. This study aims to identify the use of positive politenessstrategies by the guest in TripAdvisor review of Prime Plaza Suites Sanur Bali. This studyanalyzed qualitatively used the theory of Brown and Levinson (1987) about the types ofpoliteness strategies. The findings showed that from 15 sub-strategy in positive politenessstrategies according to theory there are only 6 strategies used by the guest in giving review theyare (1) exaggerate (interest, approval, sympathy with H), (2) Intensify Interest to H, (3) SeekAgreement, (4) Offer Promise, (5) Give or Ask Reason and (6) Give Gifts to H Goods,Sympathy, Understanding, Cooperation. The guests use a positive politeness strategy in givingfeedback about what they feel in Prime Plaza Suites Sanur Bali.Keywords: Positives Politeness Strategies, TripAdvisor Review, Prime Plaza SuitesABSTRAKPenelitian ini berjudul Positive Politeness Strategies Used by the Guest in Tripadvisor Reviewof Prime Plaza Suites Sanur Bali. Tujuan dari penelitian ini adalah untuk mengidentifikasikegunaan dari strategi kesantunan positif yang digunakan oleh tamu dalam memberikanulasan di aplikasi TripAdvisor tentang Prime Plaza Suites Sanur Bali. Penelitian ini dianalisissecara kualitatif menggunakan teori dari Brown dan Levinson (1987) tentang strategikesantunan berbahasa. Hasil penelitian menunjukkan bahwa dari 15 strategi kesantunanpositif sesuai dengan teori, hanya 6 strategi yang digunakan oleh tamu dalam membuat ulasan,diantaranya (1) melebihkan dalam memberikan komentar atau pujian (exaggerate) (2)menegaskan (Intensify Interest to H), (3) mengupayakan kesepakatan (Seek Agreement), (4)menawarkan, berjanji (Offer Promise), (5) memberi atau meminta alasan (Give or Ask Reasondan (6) memberi hadiah kepada penutur (Give Gifts to H Goods, Sympathy, Understanding,Cooperation). Tamu menggunakan strategi kesantunan positif ini dalam memberikantanggapan tentang pengalaman yang mereka rasakan selama menginap di Prime Plaza SuitesSanur Bali.Kata Kunci: Strategi Kesantunan Positif, Ulasan TripAdvisor, Prime Plaza Suites